ANALISIS PENGGUNAAN E-MODUL PADA MATA KULIAH EKOLOGI : LITERATUR REVIEW - GH, MULIANA (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
This study describes one aspect of learner needs analysis, namely a literature review on previous research regarding the use of modules in ecology learning. The research method employed is a literature review or systematic literature review (SLR), which involves examining studies that focus on the use of ecology modules in biology learning processes. The literature sources are derived from articles published in journals and proceedings. Based on the literature review findings, it was concluded that the use of modules in ecology learning has been widely implemented in classrooms. The design and development of ecology learning modules aim to enhance learners' abilities, including contextual learning, independent learning, critical thinking, and scientific literacy. The ecology learning modules identified are in the form of both traditional modules and e-modules that utilize software such as Integrated Development Environment (IDE), Electronic Publication (E-Pub), MIT App Inventor & Adobe Photoshop CS6, QR codes, Moodle, Flip Builder, Flip PDF Corporate Edition, and Sigil software. The results of this review can serve as a foundation or reference for future research on the development of ecology learning modules. ABSTRAKPenelitian ini mendeskripsikan mengenai salah satu analisis kebutuhan peserta didik, yaitu kajian literatur mengenai penelitian terdahulu tentang pemanfaatan modul dalam pembelajaran ekologi. Metode penelitian yang digunakan adalah kajian literatur atau SLR (systematic literature review), yaitu kajian literatur terkait penelitian-penelitian yang mengkaji pemanfaatan modul ekologi dalam proses pembelajaran biologi. Sumber literatur yang digunakan berasal dari artikel-artikel dari junal maupun prosiding. Berdasarkan hasil kajian literatur yang dilakukan, diperoleh kesimpulan bahwa penggunaan modul dalam pembelajaran ekologi telah banyak digunakan di kelas. Pembuatan dan pengembangan modul pembelajaran ekologi bertujuan untuk meningkatkan kemampuan belajar peserta didik, meliputi pembelajaran kontekstual, belajar mandiri, berpikir kritis, hingga literasi sains peserta didik. Modul-modul pembelajaran kajian ekologi yang ditemukan dalam bentuk modul maupun e-modul yang menggunakan software IDE (Integrated Development Environment), E-Pub (Electronic Publication), MIT Appriventor & Adobe Photoshop CS6, QR code, moodle, flip builder, flip PDF corporate edition, dan sigil software. Hasil kajian ini dapat digunakan sebagai dasar maupun referensi dalam penelitian pengembangan modul pada pembelajaran ekologi di masa yang akan datang.